2013
DOI: 10.1186/2047-783x-18-16
|View full text |Cite
|
Sign up to set email alerts
|

The effects and mechanism of ginsenoside Rg1 on myocardial remodeling in an animal model of chronic thromboembolic pulmonary hypertension

Abstract: BackgroundRecent studies haveshown that ginsenoside Rg1, extracted from the dry roots of Panax notoginseng as a traditional Asian medicine, plays an anti-fibrosis role in myocardial remodeling. However, the mechanism still remains unclear. In the present study, we investigate the effect of ginsenoside Rg1on the collagenic remodeling of myocardium in chronic thromboembolic pulmonary hypertension (CTEPH), and its potential mechanism.MethodsA rat model of CTEPH was established by injecting thrombi through the jug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 18 publications
2
26
0
1
Order By: Relevance
“…An active ingredient in an extract from the dried roots of Panax notoginseng, known for its cardioprotective effects, is ginsenoside Rg1 (Lü et al, 2009). Previous studies that have evaluated the benefits of ginsenoside Rg1 for the cardiovascular system primarily focused on its anti-remodeling (Deng et al, 2010;Li et al, 2013;Zhang et al, 2013) and anti-ischemic effects (Xia et al, 2011;Yin et al, 2011). However, to the best of our knowledge previous studies have not evaluated whether ginsenoside Rg1 can prevent myocardial injury related to DM.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…An active ingredient in an extract from the dried roots of Panax notoginseng, known for its cardioprotective effects, is ginsenoside Rg1 (Lü et al, 2009). Previous studies that have evaluated the benefits of ginsenoside Rg1 for the cardiovascular system primarily focused on its anti-remodeling (Deng et al, 2010;Li et al, 2013;Zhang et al, 2013) and anti-ischemic effects (Xia et al, 2011;Yin et al, 2011). However, to the best of our knowledge previous studies have not evaluated whether ginsenoside Rg1 can prevent myocardial injury related to DM.…”
Section: Introductionmentioning
confidence: 58%
“…The putative cardioprotective role of ginsenoside Rg1 has been the focus of several studies (Deng et al, 2010;Xia et al, 2011;Yin et al, 2011;Li et al, 2013;Zhang et al, 2013), but not with regard to the cardiovascular damage incurred in the pathogenesis of diabetes. The present study was undertaken to investigate the effects of injected treatment of ginsenoside The CASP3 and Bcl-xL proteins are stained in brown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive data from in vitro and in vivo studies indicate that G-Rg1 has antifibrotic effects in the liver [4], lung [5], and cardiac [6] fibrosis. Furthermore, some recent studies have shown that G-Rg1 may be beneficial in improving renal function and tubulointerstitial fibrosis.…”
mentioning
confidence: 98%
“…The effectiveness of PNS in attenuating chronic hypoxic pulmonary hypertension in rats has previously been reported [13]. It has been showed that ginsenoside R g1 positively affects myocardial remodeling and pulmonary hemodynamics [14]. Although PNS has effect in attenuating hypoxia hypercapnia-induced pulmonary vasoconstriction (HHPV) [15], the mechanism of how ginsenoside R g1 prevents HHPV and the form of PAH has never been reported.…”
Section: Introductionmentioning
confidence: 99%